2015
DOI: 10.1515/bot-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

First report of the red alga Gayliella fimbriata in the Mediterranean Sea

Abstract: The red alga Gayliella fimbriata (Ceramiaceae, Rhodophyta) is reported for the first time from the Mediterranean Sea. This species was collected growing as an epiphyte on Laurencia obtusa in the sublittoral zone at Antalya (Mediterranean coast of Turkey). Gayliella fimbriata is characterized by its protruding clavate gland cells. Features to distinguish the four Turkish species of Gayliella from one another are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some studies using only this morphological character have identified specimens as G. fimbriata, but the use of gland cell shape as diagnostic must be questioned, considering the results of molecular analyses (Norris , Taşkın et al. ). Gayliella womersleyi has a unique twisted apex and was supported in molecular analyses, showing this to be an informative character (Cho et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies using only this morphological character have identified specimens as G. fimbriata, but the use of gland cell shape as diagnostic must be questioned, considering the results of molecular analyses (Norris , Taşkın et al. ). Gayliella womersleyi has a unique twisted apex and was supported in molecular analyses, showing this to be an informative character (Cho et al.…”
Section: Discussionmentioning
confidence: 99%